Enhancing Access and Quality of Open Instructional Videos in Africa: Visibility of NOUN Repository on Social Media - Adelakun, Lateef A. (West African Journal of Open and Flexible Learning, 2023)
National Open University of Nigeria (NOUN) open courseware has been adjudged a source of dependable open educational resources for students and instructors within and outside the ambit of open and distant learning institutions across African sub-region and beyond. The development of instructional videos, produced by professional in every subject area in NOUN has added significant values to open learning resources. Opening the instructional videos to unrestricted access particularly through social media has been a subject of debate considering the public request and the university’s need to protect the integrity of the videos. Although, social media especially YouTube house both open and restricted access instructional videos, doubtful sources and questionable contents have made its adoption for open universal education a prolonged challenge. This work surveyed public opinions within and outside Nigeria on how social media could enhance the openness of NOUN’s instructional videos and boost the users’ trust in the contents on social media. Hanging the discussions on Uses and Gratification theoretical analysis, transporting NOUN instructional videos to social media was adjudged a welcomed development. Substantial empirical deductions from public perceptions of the idea affirmed that the practice would lubricate the public interests and confidence in open and distant education. Résumé Les didacticiels ouverts de National Open University of Nigeria (NOUN) ont été considérés comme une source de ressources éducatives ouvertes fiables pour les étudiants et les instructeurs à l’intérieur et à l’extérieur du cadre des établissements d’enseignement ouverts et à distance dans la sous-région africaine et au-delà. Le développement de vidéos pédagogiques, produites par des professionnels dans chaque domaine de NOUN, a ajouté des valeurs significatives aux ressources d’apprentissage ouvertes. L’ouverture des vidéos pédagogiques à un accès illimité, notamment via les réseaux sociaux, a fait l’objet de débats compte tenu de la demande du public et de la nécessité pour l’Université de protéger l’intégrité des vidéos. Bien que les médias sociaux, en particulier YouTube, hébergent des vidéos pédagogiques à accès libre et restreint, leurs sources et leurs contenus douteux ont fait de leur adoption pour l’éducation universelle ouverte un défi prolongé. Ce travail a interrogé l’opinion publique au Nigéria et à l’étranger sur la manière dont les médias sociaux pourraient améliorer l’ouverture des vidéos pédagogiques de NOUN et renforcer la confiance des utilisateurs dans le contenu des médias sociaux. En se basant sur l’analyse théorique de l’utilisation et de la gratification, le transport des vidéos pédagogiques du NOUN vers les médias sociaux a été considéré comme un développement positif. Des déductions empiriques substantielles des perceptions du public de l’idée ont affirmé que la pratique lubrifierait les intérêts et la confiance du public dans l’éducation ouverte et à distance. Mots-clés : vidéo pédagogique, ressources ouvertes, médias sociaux, référentiel, didacticiels.